Toward an interoperable, intraoperative situation recognition system via process modeling, execution, and control using the standards BPMN and CMMN - Junger, Denise; Just, Elisaveta; Brandenburg, Johanna; Wagner, Martin; Schaumann, Katharina Elisabeth; Klenzner, Thomas; Burgert, Oliver (International journal of computer assisted radiology and surgery, 2023)
Purpose For the modeling, execution, and control of complex, non-standardized intraoperative processes, a modeling language is needed that reﬂects the variability of interventions. As the established Business Process Model and Notation (BPMN) reaches its limits in terms of ﬂexibility, the Case Management Model and Notation (CMMN) was considered as it addresses weakly structured processes. - Methods To analyze the suitability of the modeling languages, BPMN and CMMN models of a Robot-Assisted Minimally Invasive Esophagectomy and Cochlea Implantation were derived and integrated into a situation recognition workﬂow. Test cases were used to contrast the differences and compare the advantages and disadvantages of the models concerning modeling, execution, and control. Furthermore, the impact on transferability was investigated. - Results Compared to BPMN, CMMN allows ﬂexibility for modeling intraoperative processes while remaining understandable. Although more effort and process knowledge are needed for execution and control within a situation recognition system, CMMN enables better transferability of the models and therefore the system. Concluding, CMMN should be chosen as a supplement to BPMN for ﬂexible process parts that can only be covered insufﬁciently by BPMN, or otherwise as a replacement for the entire process. - Conclusion CMMN offers the ﬂexibility for variable, weakly structured process parts, and is thus suitable for surgical interventions. A combination of both notations could allow optimal use of their advantages and support the transferability of the situation recognition system.